2002
DOI: 10.1136/gut.50.1.106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum cystatin C concentration as a marker of renal function in patients with cirrhosis of the liver

Abstract: Background and aims: Diagnosis of moderately impaired renal function is of particular importance in patients with cirrhosis of the liver. Whereas patients with a markedly impaired glomerular filtration rate can be diagnosed easily by elevated serum creatinine concentrations, moderately reduced renal function may be missed by this conventional parameter. Recently, cystatin C has been suggested as a sensitive marker of renal function, independent of sex or muscle mass. Therefore, the aim of this study was to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(124 citation statements)
references
References 20 publications
6
115
0
3
Order By: Relevance
“…Ten of these patients (62.5%) had reduced GFR (CCl<80 ml/min/1.73 m 2 ). These results were consistent with previous studies that proved serum CysC to be a better marker of GFR than serum Cr in cirrhotics [12,13]. We used measured CCl as a referent method for determining GFR because it is a reliable and not an expensive method.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Ten of these patients (62.5%) had reduced GFR (CCl<80 ml/min/1.73 m 2 ). These results were consistent with previous studies that proved serum CysC to be a better marker of GFR than serum Cr in cirrhotics [12,13]. We used measured CCl as a referent method for determining GFR because it is a reliable and not an expensive method.…”
Section: Discussionsupporting
confidence: 79%
“…Unlike serum Cr, CysC levels are independent of age, sex, muscle mass, inflammatory conditions or malignancy [4,9,10]. Several reports have suggested that increased CysC levels are more sensitive in detecting renal dysfunction in patients with cirrhosis than increased Cr levels, and that measurement of serum CysC could offer a good alternative to serum Cr for the assessment of renal function in these patients [11][12][13]. Gerbes et al found that serum CysC is more effective in detecting kidney injury in advanced cirrhotic patients than serum Cr [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, CysC was the only marker to correlate with measured GFR in all stages of hepatocellular failure (201). In addition, serum cystatin concentrations also appear to be a better marker than creatinine and the Cockcroft equation for the earlier diagnosis of renal disease in end stage liver failure (202). It has also been recommended for the follow-up of renal function after liver transplantation (203).…”
Section: Cysc and Hepatocellular Failurementioning
confidence: 99%
“…17 Indeed, recent studies have shown that cystatin C is a better marker of GFR than Scr in many disease states, including advanced liver failure and hepatorenal syndrome. [17][18][19][20][21][22] Currently, two automated assays are available that make determination of serum cystatin C level as easy and convenient as determining Scr. 23,24 In the article by Schück et al, 10 the ability of cystatin C to predict GFR in the posttransplant population was tested.…”
Section: A Tale Of Two Markersmentioning
confidence: 99%